Beyond words: Going off script in Theravada Southeast Asia. (June 2022) - Edwards, Penny
Abstract : Accounts of Buddhism in Thailand, Burma and Cambodia offer detailed descriptions of 'the power attributed to inscribed amulets, tattoos, and related forms of writing' (p. 8). But earlier scholarship on Southeast Asia 'often looked down on non-literary uses of script', treating it as either a 'non-Buddhist "cultural" accretion or the ignoble trappings of popular superstition' (p. 8). Such judgements were based on an idealised conception of Buddhism that focused on canonical scripture, and congealed under colonial rule. Where Richard Fox finds a fruitful 'indeterminacy' in the aksara of Bali, colonial scholarship tended towards overdetermination, creating a rigid hierarchy of Buddhist scriptural forms. Pali, the language in which generations of monks had chanted, thought and wrote, was deemed 'less than' Sanskrit, but 'more than' the plethora of indigenous languages of the region.